2012
DOI: 10.3109/09553002.2012.702298
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects and specific gene expression alterations induced by I-125-labeled triplex-forming oligonucleotides

Abstract: Purpose:Triplex-forming oligonucleotides (TFO) bind to the DNA double helix in a sequence-specific manner. Therefore, TFO seem to be a suitable carrier for Auger electron emitters to damage exclusively targeted DNA sequences, e.g., in tumor cells. We studied the influence of I-125 labeled TFO with regard to cell survival and induction of DNA double-strand breaks (DSB) using TFO with different genomic targets and target numbers. Furthermore, the ability of TFO to alter the gene expression of targeted genes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the radiosensitizing mechanism operating through DNA damage could be more efficient. A solution of this dilemma could be based on selective targeting of nanoparticles to specific genome sequences, like oncogenes, using appropriately designed oligo-nucleotides as being available for radio-emitters [70]. With techniques of COMBO-FISH [71,72] and PNA probe combinations [73], NPs may be transferred to cell nuclei and specifically addressed to given chromatin targets.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the radiosensitizing mechanism operating through DNA damage could be more efficient. A solution of this dilemma could be based on selective targeting of nanoparticles to specific genome sequences, like oncogenes, using appropriately designed oligo-nucleotides as being available for radio-emitters [70]. With techniques of COMBO-FISH [71,72] and PNA probe combinations [73], NPs may be transferred to cell nuclei and specifically addressed to given chromatin targets.…”
Section: Discussionmentioning
confidence: 99%
“…An additional option that has been explored for targeting of cancer cell DNA is the use of triplex forming oligonucleotides (TFO), site-specific molecules that bind to the major groove of duplex DNA to form a triplex helix. Several studies by Dahmen and Kriehuber (2012) and Dahmen et al (2016 , 2017 ) have demonstrated that TFOs can be readily labeled with radionuclides, such as 125 I and 111 In, and that these conjugates can exert site- and sequence-specific DNA damage in cancer cells.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…Another type of DNA targeting agent are the radiolabelled forms of major groove‐binding triplex‐forming oligonucleotides (TFO), which interact with specific DNA sequences. Dahmen et al used 125 I‐labelled TFOs against various DNA sequences such as GAPDH or multi‐binding site . They showed selective induction of DNA damage, selective reduction of target gene expression and reduction of clonogenic survival in vitro .…”
Section: Therapy With a Focus On Intranuclear And Dna Targetingmentioning
confidence: 99%